Scaffold-hopping for molecular glues targeting the 14-3-3/ERα complex - Konstantinidou, Markella; Zingiridis, Marios; Pennings, Marloes A. M.; Fragkiadakis, Michael; Virta, Johanna M.; Revalde, Jezrael L.; Visser, Emira J.; Ottmann, Christian; Brunsveld, Luc; Neochoritis, Constantinos G.; Arkin, Michelle R. (Nature communications, 2025)
Molecular glues, small molecules that bind cooperatively at a protein-protein interface, have emerged as powerful modalities for the modulation of protein-protein interactions (PPIs) and “undruggable” targets. The systematic identification of new chemical matter with a molecular glue mechanism of action remains a significant challenge in drug discovery. Here, we present a scaffold hopping approach, using as a starting point our previously developed molecular glues for the native 14-3-3/estrogen receptor alpha (ERα) complex. The novel, computationally designed scaffold is based on the Groebke-Blackburn-Bienaymé multi-component reaction (MCR), leading to drug-like analogs with multiple points of variation, thus enabling the rapid derivatization and optimization of the scaffold. Structure-activity relationships (SAR) are developed using orthogonal biophysical assays, such as intact mass spectrometry, TR-FRET and SPR. Rational structure-guided optimization is facilitated by multiple crystal structures of ternary complexes with the glues, 14-3-3 and phospho-peptides mimicking the highly disordered C-terminus of ERα. Cellular stabilization of 14-3-3/ERα for the most potent analogs is confirmed using a NanoBRET assay with full-length proteins in live cells. Our approach highlights the potential of MCR chemistry, combined with scaffold hopping, to drive the development and optimization of unprecedented molecular glue scaffolds. Molecular glues have great potential for drug discovery if they can be systematically discovered. Konstantinidou, et al describe a scaffold-hopping approach using multicomponent reaction chemistry to design molecular glues that induce 14-3- 3σ/ERα formation in cells.